Reproductive effects in male rats exposed to diuron - Fernandes, Glaura S. A.; Arena, Arielle C.; Fernandez, Carla D. B.; Mercadante, Amauri; Barbisan, Lufs F.; Kempinas, Wilma G. (Elsevier B.V., 2007)
Diuron is a ureic herbicide considered to have very low toxicity. The present study evaluated several aspects of reproductive toxicity of diuron in adult male rats. Diuron was diluted in corn oil and administered by oral gavage to groups of 18-20 rats at doses of 0, 125 or 250 mg/kg per day for 30 days; the control group received only the corn oil vehicle. At the end of the treatment period, approximately half the animals from each group were assigned to one of two terminal assessment lines: (1) reproductive organ, liver and kidney weights; measurement of diuron concentrations in liver and kidney; plasma testosterone determinations; evaluation of daily sperm production per testis; sperm number and sperm transit time in the epididymis; or (2) sexual behavior assessment during cohabitation with a receptive female; fertility and pregnancy outcome after natural mating; testicular, epididymal, kidney and liver histopathology; sperm morphology. After 30 days of oral diuron treatment, there were no treatment-related changes in body weights, but dose-related diuron residues were detected in the liver of all treated rats and absolute and relative liver weights were increased in both groups. There were no statistically significant differences between the treated and control groups obtained in plasma testosterone concentrations, or in parameters of daily sperm production, sperm reserves in the epididymis, sperm morphology or measured components of male sexual behavior. on the other hand, the number of fetuses in the litters from diuron-treated rats was slightly smaller than litters from control rats. Therefore, although the results did not indicate that diuron exposure resulted in direct male reproductive toxicity in the rat, they suggest that additional studies should be undertaken to investigate the possible effects on fertility and reproductive performance. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: reproductive toxicity; diuron; herbicides; sexual behavior; fertility; male rat